2008
DOI: 10.1111/j.1743-6109.2008.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive and Aversive Classical Conditioning of Female Sexual Response

Abstract: Introduction There is only limited evidence for appetitive classical conditioning of female sexual response, and to date modulation of female sexual response by aversive conditioning has not been studied. Aim The aim of this article is to study appetitive and aversive classical conditioning of sexual responses in women. Main Outcome Measures Vaginal pulse amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 29 publications
5
43
4
Order By: Relevance
“…In line with previous studies [43], [44], the analyses of VPA during the acquisition phase did not reveal a main effect of Stimulus on FIR, p < .08, and SIR, p  =  .28, whereas it did on TIR, showing that VPA was higher following the presentation of the CS+ plus vibrostimulation than following the CS−, F (1, 56) =  27.74, p < .01,  =  .33. As can be seen in Figure 2,b, the vibrostimulation resulted in a genital arousal response.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies [43], [44], the analyses of VPA during the acquisition phase did not reveal a main effect of Stimulus on FIR, p < .08, and SIR, p  =  .28, whereas it did on TIR, showing that VPA was higher following the presentation of the CS+ plus vibrostimulation than following the CS−, F (1, 56) =  27.74, p < .01,  =  .33. As can be seen in Figure 2,b, the vibrostimulation resulted in a genital arousal response.…”
Section: Resultssupporting
confidence: 90%
“…Therefore it seems that combination of a non-visual sexual US and neutral CSs is not sufficient to elicit conditioned genital responding in men. With respect to genital arousal, the present study contributes to the accumulating evidence [43], [44] that women can be sexually conditioned to initially neutral stimuli, whereas our results do not support such a straightforward mechanism in men, at least, when making use of a tactile US. However, making use of sexually explicit visual stimuli as US, conditioned responses towards an initial neutral CS (a penny jar) were observed by Plaud and Martini [46].…”
Section: Discussioncontrasting
confidence: 71%
“…Experimenters successfully conditioned sexual response using two second stimulation periods from a 2cm butterfly-style (''handsoff'') vibrator (Both et al, 2008). Laan and van Lunsen (2002) used vibratory stimulation to successfully induce orgasm in all the female participants in a laboratory study, which has been reported only in poster format to date.…”
Section: Laboratory Use Of Vibrators With Womenmentioning
confidence: 98%
“…Another mechanism that may be involved is classical conditioning [64][65][66]. Laboratory studies on women have shown that the sexual arousal response to a specific stimulus can be positively conditioned by repeatedly pairing the stimulus with pleasurable sexual stimulation.…”
Section: Disorders In Sexual Desirementioning
confidence: 98%
“…Sexual stimuli can also lose their attractiveness when sex repeatedly results in negative outcomes, such as anxiety, disappointment or pain during intercourse. Recently, a laboratory study showed that when an erotic stimulus was repeatedly followed by a pain stimulus, this suppressed the sexual arousal response and the subjective appreciation of the erotic stimulus [65].…”
Section: Disorders In Sexual Desirementioning
confidence: 99%